International steel trade. (Woodhead Pub., 1995)
This book provides a basic guide to the iron and steel industry in a single convenient reference source. The origins of steel and its manufacture are explained first, with a basic outline of the principal steel grades. The author then goes on to look at production and consumption and its commercial significance. He also analyses the global trade in steel and shows its importance to the metals industry as alloying elements and coatings. The final section considers the future for steel, the changing trade patterns, environmental issues and the threat of substitutes to the industry.